C-kit Inhibition by Imatinib Mesylate Attenuates Progenitor Cell Expansion and Inhibits Liver Tumor Formation in Mice - Knight, B.; Tirnitz-Parker, Nina; Olynyk, John (W.B. Saunders Co., 2008)
Background & Aims: Numerous studies have linked the proliferation of liver progenitor cells (LPCs) during chronic liver disease to the risk for development of hepatocellular carcinoma. Thus, selective inhibition of LPC growth during preneoplastic injury may prevent or delay the onset of liver cancer. Rats carrying a germ-line mutation in c-kit have an impaired LPC response to liver injury. Therefore, we hypothesized that the c-kit inhibitor imatinib mesylate (IM) would suppress LPC growth and, therefore, may exert antitumorigenic effects in the liver. Methods: Expression of IM target proteins was examined in chronically injured rodent and human livers. The effect of IM was examined in vitro using LPC lines and in vivo in mice fed a choline-deficient, ethionine-supplemented (CDE) diet. Livers were examined following short-term (up to 1 month) or long-term (up to 14 months) feeding of CDE diet and drug treatments. Results: C-kit was significantly up-regulated in chronic injury and expressed by LPCs. IM was antiproliferative to LPC lines, and knockdown of c-kit reduced this response. IM treatment inhibited the LPCs response and early fibrogenesis induced by a short-term CDE diet. On the longer term, IM treatment reduced the extent of fibrosis and significantly inhibited tumor formation. Conclusions: Tyrosine kinase inhibitors, such as IM, may be suited for the prevention of hepatocellular carcinoma in the setting of chronic liver injury via antiproliferative effects on c-kit-expressing LPCs.